Deuce or advantage? Examining gender bias in online coverage of professional tennis - Yip, A. (International Review for the Sociology of Sport, 2018)
Despite the increasing popularity of women`s sports, it has generally been found that female athletes receive less media coverage and are portrayed negatively with myriad gender-specific descriptors. Such biased representations warrant attention as they construct and reinforce traditional gender beliefs. This study compared the representations of female and male tennis players on the official site of the Australian Open 2015 and ESPN. A total of 357 articles were analysed using content analysis. The findings showed that gender representations on the two media outlets were quite similar as they both portrayed female players more negatively than male players by focusing on a few areas directly or indirectly: athletic weaknesses, negative skills, mental weaknesses and non-competitive roles (including appearance, attire, family and personal relationship). However, the use of certain descriptors might indicate the possibility of more gender-neutral representations of athletes in the future. It was concluded that while hegemonic masculinity was challenged at times, stereotypical beliefs about females were largely reinforced in the mediated gender representations on the two websites.